Hubungan Antara Presepsi Perawat Dengan Pelaksanaan Komunikasi Terapeutik Di Rumah Sakit Jiwa Daerah Provinsi Bangka Belitung - Tajudin Tajudin; Akhiat Akhiat; Nurhayati Nurhayati; Dudella Desnani Firman Yasin; Sammy Lazuardi Ginanjar (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Therapeutic communication is communication that is used to help heal patients. Based on the preliminary study results, nurses seem lazy to interact with patients. The nurse's skills in therapeutic communication influence the effectiveness of interventions in psychiatric crimes. The implementation of therapeutic communication is influenced by several factors. On this basis, researchers are interested in conducting research on the relationship between nurses' perceptions and the implementation of therapeutic communication by nurses. This study aimed to determine the relationship between nurses' perceptions and the implementation of therapeutic communication by nurses at the Mental Hospital in the Province of Bangka Belitung. The research method is descriptive-analytic with a cross-sectional approach which was carried out on May 23-28 2022 at the Regional Mental Hospital of the Bangka Belitung Islands Province with a total of 57 respondents. The research instrument used a questionnaire. The data analysis used was the Chi-Square test with a significance limit of α=0.05. The research results obtained that there was no significant relationship between perceptions of work experience and the implementation of therapeutic communication with a value of p = 0.203, there was no significant relationship between knowledge and the implementation of therapeutic communication with a value of p = 0.612, but there was a significant relationship between perceptions regarding attitudes and the implementation of therapeutic communication with a value of p = 0.000. It is hoped that this research can be a basis for other researchers in conducting further research.